2017
DOI: 10.2527/tas2017.0029
|View full text |Cite
|
Sign up to set email alerts
|

National Beef Quality Audit-2016: Transportation, mobility, and harvest-floor assessments of targeted characteristics that affect quality and value of cattle, carcasses, and by-products1

Abstract: The National Beef Quality Audit-2016 (NBQA-2016) was conducted to assess current transportation, mobility, and quality characteristics of U.S. fed steers and heifers. Data were collected at 17 beef processing facilities between March and November 2016. About 8,000 live cattle were evaluated for transportation and mobility, and about 25,000 carcasses were evaluated on the slaughter floor. Cattle were in transit to the slaughter facility for a mean duration of 2.7 h from a mean distance of 218.5 km using trailer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 38 publications
7
24
4
Order By: Relevance
“…In the current study, the greatest frequency of bruising was found along the dorsal midline and in the rump region ( Figure 1 ), as similarly reported in other studies ( Jarvis et al, 1995 ; Romero et al, 2013 ; Huertas et al, 2015 ; Eastwood et al, 2017 ; Harris et al, 2017 ; Lee et al, 2017 ). There are several possible explanations for bruises being most concentrated in these regions.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In the current study, the greatest frequency of bruising was found along the dorsal midline and in the rump region ( Figure 1 ), as similarly reported in other studies ( Jarvis et al, 1995 ; Romero et al, 2013 ; Huertas et al, 2015 ; Eastwood et al, 2017 ; Harris et al, 2017 ; Lee et al, 2017 ). There are several possible explanations for bruises being most concentrated in these regions.…”
Section: Resultssupporting
confidence: 91%
“…Previously published studies in the United States and Canada have reported bruise prevalence ranging from 40% and 68%, with percentages traditionally reported by animal sex class, that is, cull cows and bulls versus finished steers and heifers ( Van Donkersgoed et al, 2001 ; Eastwood et al, 2017 ; Harris et al, 2017 ; Lee et al, 2017 ). Studies outside of North America have reported larger variation in bruise prevalence among studies, ranging from 8% to 99% ( Jarvis et al, 1995 ; Marshall, 1977 ; Gallo et al, 1999 ; Costa et al, 2006 ; Andrade et al, 2008 ; Strappini et al, 2010 ; Romero et al, 2013 ; Huertas et al, 2015 ; Bethancourt-Garcia et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous years, black hided cattle tended to sell for higher prices and many producers took advantage of this opportunity for a premium on their calves. The black hide color came from an increase in use of Angus genetics, which also allows calves to qualify for various value added or branded beef programs (Wessler, 2011;Eastwood et al, 2017). Producers use specific sire breeds dependent upon their production goals, available resources, and environment.…”
Section: Introductionmentioning
confidence: 99%